TINJAUAN YURIDIS MENGENAI PENYALAHGUNAAN PERJANJIAN LISENSI HAK MEREK DAN AKIBAT HUKUMNYA MENURUT KITAB UNDANG-UNDANG HUKUM PERDATA - Anak Agung Poetri Paranity; I Nyoman Suryana (Jurnal Ilmiah Raad Kertha, 2021)
In the last decade, along with the free trade of information and communication globalization, there is no doubt that the issue of the existence of a legal system of Intellectual Property that is closely linked to technological developments, industrial growth and the smoothness of world trade is a very important issue whose existence has been globally recognized. Brands that are part of Intellectual Property Right at first are just a sign that consumers can differentiate their products or services from one another. With consumer brands it's easier to remember what's needed, and quickly determine what it will buy. In its development the role of the brand is changing. Brand is not just a sign, but a lifestyle. No brand entrepreneur can not promote his goods or services to the public at large and maximum. Likewise, people can not distinguish the quality of goods or services from one another. On the other hand, today's emerging business competition may pose a problem for brand rights where the brand is seen by business actors as one of the business opportunities in obtaining profit through unfeasible shortcuts by creating or marketing goods or products by forging or impersonating a brand -the famous brand. This can lead to an unhealthy competition. Unhealthy business competition may occur due to a transfer of brand rights, one of which may occur in a brand rights license agreement. The licensing agreements, especially those concerning the trademark, constitute a special agreement for the parties to which they are bound, as they relate to the Intellectual Property Rights which are related to each other. The license agreement is a closed agreement (tying agreement), the agreement is an agreement that is prohibited in Law No. 5 of 1999, but in the Act issues of agreement relating to Intellectual Property Rights such as brand license agreement are exempted. Since the explanation of the exclusion of the license agreement pursuant to Law Number 5 Year 1999 raises multiple interpretations or legal obscurity in the exclusion of licensing agreements relating to the rights of brands and Intellectual Property Rights so there is need to clarify the limitation of exceptions and in what respects such a license agreement excluded.